Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/ohn.229
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Analgesia and Patient Education Reduce Postoperative Opioid Consumption in Otology

Abstract: Objective This study sought to validate alternative pain management strategies that can reduce reliance on opioids for postoperative pain management in otology. Study Design Prospective cohort study. Setting Single tertiary‐care facility. Methods Adult patients who underwent outpatient otologic surgery from September 2021 to July 2022 were randomized into treatment cohorts. The opioid monotherapy cohort received a standard opioid prescription. The multimodal analgesia cohort received the same opioid prescripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 41 publications
(107 reference statements)
0
10
0
Order By: Relevance
“…Moreover, studies by Butkus et al and Dahm et al reported that 70% to 90% of patients reported keeping excess prescription opioids in their homes, which feasibly increases the possibility of abuse and diversion 15,24 . While our study did not survey patients on opioid disposal, the average amount of excess opioids was approximately 40%.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Moreover, studies by Butkus et al and Dahm et al reported that 70% to 90% of patients reported keeping excess prescription opioids in their homes, which feasibly increases the possibility of abuse and diversion 15,24 . While our study did not survey patients on opioid disposal, the average amount of excess opioids was approximately 40%.…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, studies by Butkus et al and Dahm et al reported that 70% to 90% of patients reported keeping excess prescription opioids in their homes, which feasibly increases the possibility of abuse and diversion. 15,24 While our study did not survey patients on opioid disposal, the average amount of excess opioids was approximately 40%. In the context of recent literature, this highlights the risk that opioid over-prescription poses on communities and underscores the importance of alternative pain management.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations